Malignant Teratoma Arising From Mediastinal Non-Seminomatous Germ Cell Tumor: A Rare Case Report - Verma, Nisha; Mahajan, Saurabh (Annals of Pathology and Laboratory Medicine, 2023)
Introduction: Primary mediastinal non-seminomatous germ cell tumors (NSGCT) have a worse prognosis than gonadal germ cell tumors (GCTs). Malignant transformation of teratomatous components of GCT to a somatic malignancy is rare. Materials and methods: A case of primary mediastinal NSGCT with malignant transformation of a teratoma was seen in a 23 years old male. Resected tumor specimen was received. Tissue processing was done and sections were prepared for Histo Pathological Examination. Results: Histopathology confirmed NSGCT with yolk sac and teratomatous components. Chemotherapy for GCT transiently normalized serum tumor markers with little effect on the mediastinal mass. Incomplete resection of the residual tumor revealed intermediate grade chondosarcoma. Here we discuss this rare case. Conclusion: malignant transformation to chondrosarcoma is a rare possibility which needs to be considered while managing the patient of Primary Mediastinal Germ Cell Tumors (PMGCT)